2019
DOI: 10.1109/access.2019.2916617
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Advances and Security Challenges in Emerging E-Enabled Aircraft Systems

Abstract: The continuing increase in air traffic, along with airline operators gradually adopting IP-based network technologies, has led to the transformational concept of e-Enabled or ''connected'' aircraft. This new framework envisions a single aeronautical communications architecture connecting across the entire spectrum of the aviation sector. However, due to the complex and multidimensional nature of aviation operations, no single technology can achieve the above goal. Instead, building an integrated system which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Boeing's share price plummeted by more than $30 billion in a few days [11]. Other examples of the drawbacks that emerging technologies may introduce are potential safety risks [12], network attack risks [13], high R&D costs, and uncertainty [14]. It can be observed that emerging technologies introduce a substantial level of uncertainty and have a significant influence on the rise and fall of enterprises and even that of industries.…”
Section: Ieee Transactions On Engineering Managementmentioning
confidence: 99%
“…Boeing's share price plummeted by more than $30 billion in a few days [11]. Other examples of the drawbacks that emerging technologies may introduce are potential safety risks [12], network attack risks [13], high R&D costs, and uncertainty [14]. It can be observed that emerging technologies introduce a substantial level of uncertainty and have a significant influence on the rise and fall of enterprises and even that of industries.…”
Section: Ieee Transactions On Engineering Managementmentioning
confidence: 99%
“…Cluster 5: safety, risks, and ethical considerations Among the research clusters we examined, this particular group has the second lowest population, accounting for just 6% of the articles in our sample. Several studies within this cluster focus on the impact of external interference on the functioning of machine learning algorithms, raising concerns about safety and the potential for severe consequences (Shaikh et al 2019;Swinney and Woods 2021).…”
Section: Cluster 4: Inter-industry Collaborationsmentioning
confidence: 99%
“…Additionally, we describe general and specific mitigation measures for these threats. Table 1 summarizes a comparison between our study and those documented in other related review articles [10], [16], [19]- [21]. On application of our proposed cybersecurity risk assessment methodology, the communication system with the threat of highest risk level is determined to be VHF voice communication, while that with the lowest risk level is CPDLC.…”
Section: Introductionmentioning
confidence: 96%
“…Aviation cybersecurity risk assessment can be employed to assess risk levels qualitatively and quantitatively, and therefore reduce them to acceptable levels through proposition of appropriate mitigation and control measures. A number of review articles [10], [16], [19]- [21] have proposed approaches for addressing cybersecurity in air navigation systems. The authors of [16] sought to address potential cyber-attacks of ADS-B and SWIM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation